1996
DOI: 10.1128/jb.178.23.6651-6657.1996
|View full text |Cite
|
Sign up to set email alerts
|

Role of mismatch repair in the Escherichia coli UVM response

Abstract: Mutagenesis at 3,N4 -ethenocytosine (C), a nonpairing mutagenic lesion, is significantly enhanced in Escherichia coli cells pretreated with UV, alkylating agents, or H 2 O 2 . This effect, termed UVM (for UV modulation of mutagenesis), is distinct from known DNA damage-inducible responses, such as the SOS response, the adaptive response to alkylating agents, or the oxyR-mediated response to oxidative agents. Here, we have addressed the hypothesis that UVM results from transient depletion of a mismatch repair a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

1996
1996
2000
2000

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 50 publications
0
14
0
Order By: Relevance
“…Subsequent work confirmed that UVM (for UV modulation of mutagenesis) response did not require any of the genes known to be required for SOS mutagenesis ( Palejwala et al ., 1995 ). UVM does not appear to arise from a depletion of known mismatch repair activities ( Murphy et al ., 1996 ). The preponderance of evidence indicates that the UVM effect results from a transient alteration of the DNA replication environment.…”
Section: The Uvm Responsementioning
confidence: 99%
“…Subsequent work confirmed that UVM (for UV modulation of mutagenesis) response did not require any of the genes known to be required for SOS mutagenesis ( Palejwala et al ., 1995 ). UVM does not appear to arise from a depletion of known mismatch repair activities ( Murphy et al ., 1996 ). The preponderance of evidence indicates that the UVM effect results from a transient alteration of the DNA replication environment.…”
Section: The Uvm Responsementioning
confidence: 99%
“…Although base-or nucleotideexcision repair is probably after translesion synthesis, such repair would be futile because the mutation has already been fixed. Hypothetical postreplicative mismatch-repair mechanisms can account for the UVM effect Wang et al, 1995), but our data so far do not reveal a requirement for any of the known E. coli mismatch-repair activities for UVM (Murphy et al, 1996). On the other hand, a previously unrecognized (hypothetical) non-excisive repair mechanism can account for UVM in the following scenario.…”
Section: Discussionmentioning
confidence: 43%
“…UVM has been shown to be distinct from known DNA damageinducible E. coli responses, including the SOS response , the adaptive response to alkylation damage , as well as cellular responses to oxidative stress mediated by the oxyR gene . The UVM response does not require DNA polymerase I or DNA polymerase II , and cannot be readily accounted for by simple repair-depletion models (Murphy et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…This finding has been interpreted to mean that induced SOS proteins are required only under specific circumstances to overcome the polymerase cycling forced by normal editing at lesion sites. We have noted previously that the preponderance of evidence indicates that the UVM response is mediated through an alteration of DNA replication (13). Mutation fixation at εC residues was reported to be increased in mutD5 cells to the same extent as in UV-irradiated cells (11).…”
Section: Discussionmentioning
confidence: 97%
“…UVM appears to significantly affect mutagenesis at class 2 noninstructive lesions such as εC and possibly 1,N 6 -ethenoadenine but not at mispairing lesions such as O 6 -methylguanine (19). The mechanisms underlying the UVM response are not known, but the prepon-derance of evidence points to the transient induction of an error-prone replication activity (12)(13)(14)17).…”
mentioning
confidence: 99%